PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA ORGANISASI PADA LAPAS KELAS IIA LHOKEUMAWE - Dicky Gunawan, Muhammad; Arief Syarifuddin, Evi (IndOmera, 2024)
The research was carried out at the Class IIA Lhokseumawe Prison, with the aim of examining the influence of organizational culture factors, employee job satisfaction and organizational climate on organizational performance. The research uses an associative quantitative approach with statistical analysis tools with path analysis models. The research results found, (1) Cultural factors, employee job satisfaction and organizational climate were correlated and contributed simultaneously to organizational performance in the Class IIA Lhokseumawe Prison 64.7%. (2) Partially, the direct and indirect impact of organizational culture on organizational performance is 59.75%, while the influence of job satisfaction is 45.5% and the influence of organizational climate on organizational performance is 54.03%.